Kenneth Burke's Permanence and Change : A Critical Companion - George, Ann, 1957- (Book collections on Project MUSE., 2018)
"Since its publication in 1935, Kenneth Burke's Permanence and Change, a text that can serve as an introduction to all of Burke's theories, has become a landmark of rhetorical study. Using new archival sources and by contextualizing the theory in the past and present, Ann George offers the first sustained exploration of Burke's work and seeks to clarify the notoriously difficult book for both amateurs and scholars of rhetoric in Kenneth Burke's Permanence and Change: A Critical Companion"--